The clinical features and prognosis of chronic posthypoxic myoclonus. - Werhahn, K; Brown, P; Thompson, P; Marsden, C (1997)
The clinical and neurophysiologic features of 14 patients with chronic posthypoxic myoclonus are presented. Patients were first seen a mean of 2.5 years (range, 2 to 105 months) after the hypoxic event and followed up for 3.7 years (range, 7 to 84 months) thereafter. All patients had had a cardiorespiratory arrest, most caused by an acute asthmatic attack (11 cases). All patients had multifocal action myoclonus. Eleven patients had additional stimulus-sensitive myoclonus. There was late improvement in the myoclonic syndrome and the level of disability in all but one patient. Three patients were eventually able to discontinue antimyoclonic medication, and five patients were able to walk unaided. Cognitive deficits were found in seven patients and were usually mild. Other neurologic deficits were rare. Electrophysiologic investigation confirmed cortical action myoclonus in every case, although this could be combined with cortical reflex myoclonus, an exaggerated startle response, or brainstem reticular reflex myoclonus. We conclude that posthypoxic myoclonus typically consists of multifocal cortical action myoclonus that improves with time. It is only rarely associated with severe additional neurologic deficit.